Kaitan antara Religiusitas dan Harga Diri dengan Perilaku Menyontek pada Siswa Sekolah Berbasis Pondok Pesantren - Manzila Hesti Apriliani; Yudho Bawono (Jurnal Psikologi, 2025)
The purpose of this study was to determine the relationship between religiosity and self-esteem with cheating behavior in Islamic boarding schools. Using purposive sampling technique with 307 samples. Data collection with three research scales, namely religiosity scale, self-esteem scale, and cheating behavior scale. Correlation data analysis in this study using SPSS 23 for windows with data analysis method using Spearman Rank statistical test on the relationship between religiosity and cheating behavior obtained a significance result of 0.000 (<0.05), meaning that there is a significant relationship between religiosity and cheating behavior in students in Islamic boarding schools. Then on the relationship between self-esteem and cheating behavior obtained a significance result of 0.000 (<0.05), meaning that there is a significant relationship between self-esteem and cheating behavior in students in Islamic boarding schools. The level of strength of the relationship in the study is classified as weak because only a correlation coefficient (r) value of 0.326 was obtained. then the correlation coefficient value was obtained on the variables of religiosity and self-esteem towards cheating behavior of 0.106 or 10.6%, meaning that there is still 89.4% determined by other variables.